FAO fisheries synopsis N125: Vol.17: Pearl perches of the world ( Family Glaucosomatidae ): An annotated and illustrated catalogue of the pearl perches known to date - Ronald J McKay (FAO, 1997)
This is the 17th issue in the FAO series of world-wide annotated and illustrated catalogues of the groups of marine organismas that enter marine fisheries. This volume covers all four species currently recornized in the family Glaucosomatidae ( pearl perches ). It includes a glossary of technical terms, general remark on the family, an illustrated key to species detailed accounts of species, and a table of species by major fishing areas. Species accounts include illustrations, scientific and vernacular names references to scientic names, information on habitat, biology and isheries, and a distribution map. The work is fully indexed and a reference to pertinent literature is appended.